Pengaruh Kebiasaan Bermain Game Online terhadap Prestasi Belajar Siswa SD 1 Keruak - Bustani (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
This research is a literature review that aims to understand the impact of online games on the learning achievement of elementary school students. The method used in this research is library research or literature review. Data analysis was carried out through data simplification, data presentation, and drawing conclusions based on existing data. Data was collected by reading and recording important information contained in various journals related to the research topic. The results of the study show that addiction to playing online games can affect children's learning achievement. Thus, it can be concluded that there is a relationship between the habit of playing online games and the learning achievement of elementary school students.